The sources, distribution and toxicological effects on humans of polyhalogenated carbazoles (PHCZs) as a novel pollutant - Xiao-Xuan Wang; Dai-Jun Zhang; Shao-Yan Liu; Hui Xin; Jin-Ling Guan; Yin-Feng Zhang; Rui Zhang (Ecotoxicology and Environmental Safety)
Polyhalogenated carbazoles (PHCZs) are a new type of organic pollutants, characterized by its environmental persistence, bioaccumulation property, and toxicity similar to dioxins. The pervasive environmental presence of PHCZs, coupled with their heterogeneous spatial distribution, has garnered increasing scientific attention. Furthermore, studies have detected PHCZs in humans and demonstrated their toxic effects. Therefore, this study aims to conduct a more in-depth investigation and analysis of the systemic toxicity of PHCZs in humans and their specific molecular mechanisms. This review delves into the toxicological effects of PHCZs on humans, categorizing them into cardiotoxicity, neurotoxicity, hepatotoxicity and endocrine disruption. It also explores their metabolic transformation in the human body, ecotoxicological effects and potential degradation strategies. The content covers analytical methods, environmental occurrence patterns, ecological impacts, degradation mechanisms and prevention and control measures. This work clarifies the specific toxicological effects of PHCZs on humans, provides new therapeutic directions for future disease treatment, and enhances the environmental risk assessment and management of PHCZs.